Managing Pulmonary Edema and Electrolyte Imbalance in Advanced Chronic Kidney Disease: A Case Report - Anggreheni, Putri Dwi; Suryaningsih, Retno (Universitas Muhammadiyah Surakarta, 2024)
Background: Chronic kidney disease (CKD) is a progressive disorder that leads to fluid overload and electrolyte imbalances, increasing the risk of pulmonary edema, hyperkalemia, and hyponatremia. These complications contribute to high morbidity and mortality, necessitating a multidisciplinary approach for optimal management. Case Descriprion: A 74-year-old female with stage V CKD presented with acute respiratory distress and severe dyspnea due to pulmonary congestion. Laboratory tests revealed hyperkalemia (6.76 mEq/L), hyponatremia (129 mEq/L), and metabolic acidosis. Chest X-ray confirmed bilateral pulmonary edema, while ECG showed peaked T waves, indicating potassium-induced cardiac instability. Initial management with loop diuretics failed, requiring urgent hemodialysis for fluid removal and electrolyte correction. Calcium gluconate, insulin-dextrose, and potassium binderswere used to control hyperkalemia, while fluid restriction and slow sodium correction were implemented for hyponatremia. The patient showed significant improvement within 48 hours, with stabilization of respiratory function and electrolyte levels. Discussion: Pulmonary edema in CKD results from volume overload, RAAS activation, and endothelial dysfunction, while electrolyte imbalances arise from impaired renal excretion. Management involves diuretics, dialysis, and targeted electrolyte correction. Emerging therapies such as SGLT2 inhibitors and novel potassium binders offer promising outcomes. Conclusion: This case highlights the importance of early intervention, hemodialysis, and precise electrolyte management in CKD patients with pulmonary edema. Future research should focus on personalized nephroprotective strategies to enhance patient outcomes.